Utilization of Context in the Speech Acts of Nine Year Old Children in Family Environment - Kharisma Restiani (Institute of Multidisciplinary Research and Community Service, 2023)
Abstract: The use of language also occurs in children. Children at their age will experience different stages of language development. Children essentially have similarities and differences in language. The language shown will affect them in communicating. This study aims to describe the utilization of conversational contexts for nine-year-old children when communicating with family members. A descriptive qualitative approach was used in this study. According to the research findings, both direct and indirect speech acts such as asking, making, and defending oneself ar supported by the use of speech contexts in various ways to ensure their success. Keywords: children, utilization of context, speech.